PELATIHAN MENDONGENG BAGI SISWA/I MTS NEGERI DAN SWASTA KOTA PADANG - Riza, Armilia; Afriyanti, Rika; Sevrika, Hevriani (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2024)
The objective of this community service initiative is to conduct storytelling training to enhance the English-speaking skills of students from both public and private Islamic Junior High Schools (MTS) in Padang City, in collaboration with the English Subject Teacher Forum (MGMP Bahasa Inggris) for public and private MTS in Padang City. This initiative is based on the common challenges faced by many English teachers in encouraging students to speak English confidently, especially when speaking in front of an audience. Therefore, the community service team from the English Education Program at Universitas PGRI Sumatera Barat aims to provide English storytelling training for MTS students in Padang City, in collaboration with MGMP Bahasa Inggris for public and private MTS, with the training centered at MTS Negeri 6 Padang City. This community service activity not only focuses on teaching students how to tell stories in English but also provides strategies and techniques for effective English storytelling